PENDIDIKAN PANCASILA SEBAGAI UPAYA MEMBENTUK KARAKTER MILENIAL YANG BERTANGGUNG JAWAB - Aqilah Nurul Fawzah; Zatil Aqmarina F; Zaenul Slam (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to examine the role of Pancasila as the foundational state philosophy and as a guiding principle in shaping the character of the Indonesian nation. The focus of the research lies in the development of character based on responsibility, defined as an individual’s ability to carry out tasks diligently and to accept the consequences of their actions. The millennial generation is expected to make sound decisions and take responsibility for the outcomes of their actions, although in reality, many have yet to consistently demonstrate this capacity. To achieve these objectives, this study employs a qualitative approach through a literature review method. Data are collected from various reliable sources, including books, scholarly articles, journals, and relevant online resources. The collected information is then thoroughly read, understood, synthesized, and analyzed to provide a comprehensive understanding of the role of Pancasila in fostering a sense of responsibility among the younger generation. Consequently, the study not only highlights the theoretical significance of Pancasila but also emphasizes its practical relevance in shaping morally responsible, conscientious, and socially aware young individuals who can contribute positively to society and the nation.